Análise imunoistoquímia dos marcadores da via de sinalização WNT (Wnt10b e B-Catenina) em granulomas periapicais, cistos radiculares e cistos radiculares residuais - Lima, Catarina Pereira Monteiro (2021)
Introduction: WNT/ β-Catenin signaling pathway is envolved for several physiological and pathological processes, however its participation in bone resorption resulting from periapical lesions still remains to be uncompletely elucidated. Objectives: To evaluate the immunoexpression of Wnt10b and β-Catenin in periapical granulomas (PGs), radicular cysts (RCs) and residual radicular cysts (RRCs), correlating them with the pattern of epithelial lining and the degree of inflammatory infiltrate. Materials and methods: 60 specimens (20 PGs, 20 RCs and 20 RRCs) were selected for morphological analysis, according to the type of epithelium (atrophic/hyperplastic) and degree of inflammatory infiltrate (grade I, II and III). Immunohistochemical analysis with anti-β-Catenin and anti-Wnt10b antibodies was quantitatively evaluated in epithelium and connective tissue, considering the cell compartment (nucleus, cytoplasm and membrane). For statistical analysis, the Mann-Whitney and Spearmann correlation tests were used, considering the significance of p<0.05. Results: Regarding β-catenin in connective tissue, cytoplasmic immunoexpression was observed in all cases of PG, RC and RRC, with significantly higher expression in RC, both in cytoplasm and in nucleus (p < 0.05). In the epithelial lining, there was a predominance of membrane and cytoplasmic immunoexpression in most RCs and RRCs, and with significantly higher expression in RC, both in membrane and in cytoplasm (p < 0.05). There was also a significant association of β-catenin cytoplasmic immunoexpression in lesions with grade III inflammatory infiltrate (p < 0.05). Regarding Wnt10b in connective tissue, there was a predominance of cytoplasmic and nuclear immunoexpression in cases of PG, RC and RRC, and with significantly lower expression in RRC when compared to PG and RC, both in cytoplasm and in nucleus (p < 0.001). In the epithelial lining, it was evidenced that RRCs had higher cytoplasmic expression and lower nuclear expression for Wnt10b (p < 0.05). There was a significant association of Wnt10b cytoplasmic immunoexpression with grade III inflammatory infiltrate lesions (p < 0.05) and membrane immunoexpression with hyperplastic epithelial cysts (p < 0.05). Conclusion: The participation of WNT10b/ β-Catenin signaling pathway was evidenced in the pathogenesis of periapical lesions, and it suggests your possible role pro-inflammatory.